OBTAINING METALLURGICAL COKE PETROLEUM COKE WITH IMPROVED ENVIRONMENTAL AND PERFORMANCE CHARACTERISTICS - Qodirova Feruza; No’monova Sohiba; Mo’ydinova Nilufar; Mukhtaraliyeva Mukhtasar (Journal of new century innovations, 2022)
Abstract. The article provides information about the process of using coal, which is one of our natural resources that is a problem today. Coal is also very important in the metallurgical industry. The result of this is fully considered in the article.